Abbreviation in Social Media Account Status on Instagram - @Dasadlatif1212: A Morphological Approach - Wa Ode Halfian; Silvani Rintan Ramadani; Fina Amalia Masri (Soshum: Jurnal Sosial dan Humaniora, 2023)
This research discussed “Abbreviation Process in Social Media Status on Instagram @dasadlatif1212 (Review of Morphology Aspect)”. This research is motivated by the widespread modification of the Indonesian language in social media status, both from ordinary people, celebrities, and religious leaders who are active on social media. This research aimed to describe the abbreviation process in social media status on Instagram @dasadlatif1212. This research method used a qualitative descriptive method with a morphological approach. The data in this study were in the form of words or sentences containing abbreviations written in 2020, while the source of data in this study was the status written by the Instagram account @dasadlatif1212. The results show that there are four abbreviation processes in the status of the social media account Instagram @dasadlatif1212, namely the process of letter retention, syllable retention, letter retention, and syllables and word abbreviations that summarize the basic lexeme or lexeme combination.